Port operations and container terminal management with applications - Guldogan, Evrim Ursavas (VDM Verlag Dr. Muller, 2010)
This book explains the port operations and proposes approaches that aim to improve the most important successive steps in container terminal management activities. A multi-period assignment problem that seeks to allocate vessels to berthing spaces and quay cranes is proposed to handle the quayside operations. Subsequently, on the yard side, a discrete-event simulation model for the real life detailed processes performed during the handling of import containers is developed. In particular, the model focuses on the storage assignment problem at the operational level in a container terminal with a multiple-berth structure. An approach by means of a hierarchical structure is adapted to partition the assignment problem into two sub-problems and solve each of them using separate decision rules. Suggested storage policies are evaluated in view of the overall performance of the container terminal.